Student Underperformance in Azerbaijan: Who is to Blame and What to Do? - U.T. Mikayilova; G.Z. Huseynzada (Moscow State University of Psychology and Education, 2023)
This study provides an overview of education reforms in Azerbaijan since gaining independence, as well as a review of the dynamics of school success in the country based on data from final exams in lower secondary schools. The results of these exams show that despite the implemented reforms, students' academic success is not improving. The authors present factors that leading national education experts participating in research believe play a decisive role in students' success in school. These factors include the quality of teachers, their education, and professional development; standardized testing of students upon graduation from school; as well as school evaluations. The authors present a comparative analysis conducted on the identified "influence" factors in relation to data from international studies, as well as changes in national education policies and practices in terms of their effectiveness in ensuring successful school learning. The diagnosis of the national education system, using the RISE Systems Framework instrument (Research on Improving Education Systems), revealed that the alignment of all system elements in the reform process around academic success raises questions. The research findings may be useful for education policymakers, both in analyzing past reforms and in developing subsequent coherent changes in education policies aimed at enhancing students' success.